ANALISIS KESULITAN SISWA DALAM PENGGUNAAN KATA PENGHUBUNG PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS IV - Ria, Ersa Jusi; Khoiri, Ahmad (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
This study aims to describe the difficulties experienced by students in using conjunctions and to analyze the factors that cause these difficulties in Indonesian language learning at the elementary school level. This research used a qualitative approach with a descriptive method. The subjects of this study were 19 fourth-grade students of SDN 05 Beloyang. Data were collected through observation, interviews, and documentation. The data were analyzed through the stages of data reduction, data display, and conclusion drawing. The validity of the data was tested using source triangulation and technique triangulation. The results showed that some students were familiar with several conjunctions such as and, but, and because, but they were not yet able to use them appropriately according to their functions and sentence contexts. The difficulties experienced by students included understanding the functions of conjunctions, choosing the appropriate type of conjunction, and placing conjunctions correctly in sentences. In addition, students had difficulty distinguishing between coordinating and subordinating conjunctions. These difficulties were influenced by several factors, including limited reading and writing skills, lack of practice in constructing sentences, limited learning media or teaching materials, and a less supportive learning environment. Therefore, teachers need to implement varied teaching methods, provide regular writing exercises, and utilize engaging learning media to improve students’ understanding of conjunction usage. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan kesulitan yang dialami siswa dalam penggunaan kata penghubung serta menganalisis faktor-faktor yang menyebabkan kesulitan tersebut pada pembelajaran Bahasa Indonesia di sekolah dasar. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Subjek penelitian adalah siswa kelas IV A SDN 05 Beloyang yang berjumlah 19 orang. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, serta penarikan kesimpulan. Keabsahan data diuji melalui triangulasi sumber dan triangulasi teknik. Hasil penelitian menunjukkan bahwa sebagian siswa telah mengenal beberapa kata penghubung seperti dan, tetapi, dan karena, namun belum mampu menggunakan kata penghubung secara tepat sesuai fungsi dan konteks kalimat. Kesulitan yang dialami siswa meliputi pemahaman fungsi kata penghubung, ketepatan dalam memilih jenis konjungsi, serta penempatan kata penghubung dalam kalimat. Selain itu, siswa juga mengalami kesulitan dalam membedakan konjungsi koordinatif dan subordinatif. Faktor penyebab kesulitan tersebut antara lain kemampuan membaca dan menulis siswa yang masih perlu ditingkatkan, kurangnya latihan dalam menyusun kalimat, keterbatasan media atau bahan ajar, serta lingkungan belajar yang kurang mendukung. Oleh karena itu, diperlukan upaya guru melalui penggunaan metode pembelajaran yang bervariasi, pemberian latihan menulis secara rutin, serta pemanfaatan media pembelajaran yang menarik agar pemahaman siswa terhadap penggunaan kata penghubung dapat meningkat.